. Genre and poetic contaminations of modern novels in verse (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article deals with novels in the verse at the beginning of the twenty-first century with the author's genre nomination novel-song G. Ljutyi «Mama-Maria» and when  people say, the heart is in the pain I. Kozak «The tracks of epochs» in the aspect of genre and poetic contamination arising from the interference of works of folk work and Fiction.
Keywords: genre; novel in verse; contamination; folklore; synthesis